Epidemiology of symptoms of common mental disorders among elite Gaelic athletes: a prospective cohort study - Gouttebarge, V.; Tol, J. L.; Kerkhoffs, G. M. M. J. (The Physician and Sportsmedicine, 2016)
Objective: Scientific knowledge about symptoms of common mental disorders among elite Gaelic athletes is lacking. Consequently, this study aimed to (i) determine the prevalence, comorbidity and 6-month incidence of symptoms of common mental disorders (distress, anxiety/depression, sleep disturbance, adverse alcohol use) among elite Gaelic athletes and (ii) evaluate their association with potential stressors (severe musculoskeletal injuries, surgeries, recent life events, career dissatisfaction).